INSTITUTIONAL SUPPORT FOR INNOVATIVE MODERNIZATION OF THE TECHNICAL BASE OF THE AGRICULTURAL SECTOR OF UKRAINE (INNOVATIVE ECONOMY, 2023)
Svynous I.V., Khakhula B.V., Svynous N.I. INSTITUTIONAL SUPPORT FOR INNOVATIVE MODERNIZATION OF THE TECHNICAL BASE OF THE AGRICULTURAL SECTOR OF UKRAINEPurpose. The aim of the article is to offer practical recommendations for improving institutional support, in particular, state support for innovative modernization of their technical base based on the generalization of the research of scientists and the activities of farms in the corporate sector of the agrarian economy,Methodology of research. General scientific and special methods of economic research were used in the process of conducting the research, in particular: systemic approach − when studying the connections between phenomena and processes in the system of investment activities of agricultural enterprises; statistical analysis − when determining the dynamics of investments in agricultural enterprises; grouping − to determine the influence of various factors on the level of development of investment activity in small, medium and large enterprises; comparative − to compare investment processes in different time periods in order to identify a cause-and-effect relationship; dialectical, abstract and logical − when making theoretical generalizations, forming conclusions.Findings. It has been established that the priorities of investment activity for large, medium and small agricultural enterprises have become the implementation of capital investments, which serves as proof of their orientation towards the technical and technological modernization of the production base. Among the restraining factors of the development of investment activities, the following are highlighted: insufficient level of provision of own financial resources, imperfection of the regulatory and legal framework. Insufficient investments in increasing soil fertility and lack of economic interest in the implementation of ecologically oriented investment projects were noted.Originality. The directions for the modernization of the technical base of farms of the corporate sector of the agrarian economy in the post-war period of the country's revival, which involves improving the functioning of institutions, primarily methods of state support and the formation of prerequisites for attracting investments on the basis of public and private partnership, are substantiated.Practical value. The proposed recommendations can be used in the development of perspective plans for the development of small, medium and large agricultural enterprises, as well as in the preparation of state and regional programs for the comprehensive development of rural areas in the post-war period of the revival of the country's economy.
Keywords: innovation; institution; technical base; agricultural sector; investment; state; lending